THE DEVELOPMENT OF METAPHOR IN CONTEMPORARY RUSSIAN LITERATURE (Eureka Journal of Language, Culture & Social Change, 2026)
Metaphor has long occupied a central position in Russian literary tradition, serving not only as an aesthetic device but also as a cognitive and cultural instrument. In contemporary Russian literature, metaphor has undergone significant transformation due to socio-political change, postmodern aesthetics, and evolving linguistic consciousness. This article explores the development of metaphor in Russian literature from the late twentieth century to the early twenty-first century, focusing on its stylistic, semantic, and ideological functions. By examining key trends and representative authors, the study demonstrates how metaphor reflects new modes of thinking, identity formation, and artistic experimentation in modern Russian prose and poetry.
Keywords: Metaphor, contemporary Russian literature, postmodernism, literary language, symbolism